Legal Perspective of Using Philanthropy Approach for Low Income Household in Accessing Sufficient House in Indonesia - Efridani Lubis; Astriana Sinaga (Faculty of Law, Sriwijaya University, Indonesia, 2018)
By 2016, the backlog for housing is estimated around 13,8 million units. With the need growth 5% per year approximately, Indonesian people need 1 million houses per year. Adding to the number of backlog, it is around 1,55 million houses should be provided every year in order to meet the need in the year 2030. The number is based on the ability to pay in general of Indonesian people, which is with the price for sufficient house estimated to be 135 million rupiahs. This means low income household is out of consideration, therefore this group cannot afford the house whatsoever. In order to narrower the gap, the Government of Indonesia has built „One Million Houses Program‟ which has composition 70% for low income household. However, the program has not optimal yet. From the data from the Public Work and Housing Ministry, it is only 80% of the 1 million houses targeted that can be achieved; and from this 80%, only 569.382 units or 70,72% for the low income household. With this trend, it is difficult for the low income household to access sufficient houses in turn. The solution for this can be two alternatives: (1) the Government provide affordable houses for the group, or (2) increasing the ability to pay of the group. The alternative (1) could be difficult due to the limited budget of the Government. The possible answer is to increase the ability of the low income households, so that they can access houses either under subsides scheme from the Government or developers. In doing so, the main problem is to collect or acquire the funding for accessing the house. Using various regulations and policies that could make possible for low income households to receive the money, such as corporate social responsibility, zakat, or even philanthropy activities in Indonesia, the burden could be lessen. The importance of giving the low income households opportunity to access sufficient house is a notion that a sufficient housing can be a strategic toll for improving citizen life which becomes a background argument in the Law No. 1 of 2011 of Housing.